1998
DOI: 10.1021/bi9812322
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Modulation of Troponin T by Configuration of the NH2-Terminal Variable Region and Functional Effects

Abstract: Troponin T (TnT) is an essential element in the thin filament-based regulatory system of striated muscle. Alternative mRNA splicing generates multiple TnT isoforms with primary structural differences in the NH2-terminal region. The functional significance of this hypervariable NH2-terminal domain and the developmental or muscle type-specific TnT isoforms is not fully understood. We have analyzed chicken breast muscle TnT containing a metal-binding cluster [H(E/A)EAH]4-7 (Tx) in the NH2-terminal region to demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(153 citation statements)
references
References 40 publications
4
149
0
Order By: Relevance
“…We have successfully applied this approach for structurefunction analysis of troponin T [41,45]. The epitope analysis Serine-175-based conformational modulation of calponin mAb epitope analysis clearly showed that the molecular conformation of calponin is reconfigured by phosphorylation and S175A substitution, supporting the regulatory function of serine-175.…”
Section: Antibody Epitope Analysis To Monitor Calponin Conformationalmentioning
confidence: 89%
See 1 more Smart Citation
“…We have successfully applied this approach for structurefunction analysis of troponin T [41,45]. The epitope analysis Serine-175-based conformational modulation of calponin mAb epitope analysis clearly showed that the molecular conformation of calponin is reconfigured by phosphorylation and S175A substitution, supporting the regulatory function of serine-175.…”
Section: Antibody Epitope Analysis To Monitor Calponin Conformationalmentioning
confidence: 89%
“…Similar to the procedures which we have developed for studying troponin T isoforms [41], ELISA-based actin-calponin and tropomyosin-calponin binding assays were developed to characterize the interactions of calponin with the actin thin filament. As illustrated in Figure 2(C), microtitre plates were coated at 4 mC overnight with purified chicken gizzard actin and tropomyosin (alone or together at a molar ratio of 7 : 2, corresponding to the association of seven actins to a tropomyosin dimer) in buffer A.…”
Section: Elisa-mediated Solid-phase Protein-binding Experimentsmentioning
confidence: 99%
“…Bovine cardiac TnI purified from ventricular muscle [10] and mouse cardiac/slow TnC purified from bacterial culture [10] were used as controls. The resulting gels were stained with Coomassie Brilliant Blue R250 to reveal the resolved protein bands and duplicate gels were electrically blotted to nitrocellulose membranes as previously described [18]. After blocking in 1% bovine serum albumin, the nitrocellulose membranes were incubated with an anti-cardiac TnI monoclonal antibody (mAb) at 4°C overnight.…”
Section: Sds-polyacrylamide Gel Electrophoresis and Western Blottingmentioning
confidence: 99%
“…After blocking in 1% bovine serum albumin, the nitrocellulose membranes were incubated with an anti-cardiac TnI monoclonal antibody (mAb) TnI-1 [19] at 4°C overnight. The membranes were then repetitively washed under high stringency using Tris-buffered saline containing 0.5% Triton X-100 and 0.05% SDS, incubated with alkaline phosphatase-labeled anti-mouse IgG second antibody (Sigma Chemical Co.) at room temperature for 1 hour, washed again as above, and developed in 5-bromo-4-chloro-3-indolylphosphate/nitro blue tetrazolium substrate solution as previously described [18].…”
Section: Sds-polyacrylamide Gel Electrophoresis and Western Blottingmentioning
confidence: 99%
“…The different isoforms also show differing actomyosin ATPase activity within the sarcomeres. Exclusion of the 10 amino acids in adult cTnT, encoded by exon 5, results in significant changes in activation of the actomyosin ATPase when compared to the embryonic isoforms [8,9]; not surprisingly, much smaller functional differences are observed from alternate splicing of exon 4 in bovine cardiac troponin T [10].…”
Section: Introductionmentioning
confidence: 99%